1988
DOI: 10.2170/jjphysiol.38.819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical stretch on the membrane potential of guinea pig ventricular muscles.

Abstract: We studied the effect of stretch on the membrane potentials and ultrastructure of isolated ventricular papillary muscles of guinea pigs. The muscles were stimulated at 0.5 Hz and stretched stepwise from slack length (90% of Lmax) to 100% (mild stretch), 110-120% (moderate stretch), and 130-140% of Lmax (severe stretch), under microscopic control. In control Tyrode solution (K + = 5.4 mM, Ca2 + =1.8 mM, Mg2 + = 0.5 mM), the mild to moderate stretch significantly depolarized the resting potential (RP) by about 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
(36 reference statements)
1
7
1
Order By: Relevance
“…The muscle length corresponding to 50 mg increase of RT in the control condition (Fig. 5, left) was equivalent to the stretch of up to about 120% of Lma x (a stretch by 20%), as reported previously [17].…”
Section: Modification Of Tt-r T Relationship By Elastasesupporting
confidence: 86%
See 2 more Smart Citations
“…The muscle length corresponding to 50 mg increase of RT in the control condition (Fig. 5, left) was equivalent to the stretch of up to about 120% of Lma x (a stretch by 20%), as reported previously [17].…”
Section: Modification Of Tt-r T Relationship By Elastasesupporting
confidence: 86%
“…Thus, the use of this preparation is suitable for examining the relationship between sarcomere length and contractile tension. The relationship between resting tension (RT) and muscle length is found to be essentially linear within a certain range of muscle length in the guinea pig ventricular papillary muscle [17]. RT of the preparation is maintained, for the most part, by the parallel elastic component of the contractile protein.…”
Section: Decrease Of Resting Tension By Elastasementioning
confidence: 99%
See 1 more Smart Citation
“…Many reports indicate that stretch causes a depolarization of the RP of cardiac myocyte. 3,7,72 In the present study the RP of the myocytes was not significantly altered by moderate stretch, neither in experiments nor in the model. The reason for this was that only a very small SA current (depolarizing current) is needed to reproduce the normal physiological time-dependent changes in rat atrial function.…”
Section: Electrical Activity Of the Myocyte During Stretchcontrasting
confidence: 68%
“…Theoretical (Kim, 1992;Ruknudin et al 1993;Van Wagoner, 1993) or chloride channel (Hagiwara et al 1992;Sorota, 1992;Tseng, 1992) recently reported. Another scenario is that non-selective mechanosensitive channels having a more positive reversal potential may exist, but their effect is countered by another stretch-sensitive potassium channel, which would tend to hyperpolarize the cell membrane, as has been described in guinea-pig papillary muscle (Nakagawa, Arita, Shimada & Shirabe, 1988). These and other possibilities are discussed again later in this section.…”
Section: Discussionmentioning
confidence: 84%